Molecular dynamics of iso-amyl bromide by dielectric spectroscopy, and the effects of a nonpolar solvent, 2-methylpentane, on the spectral features - VIJ, JAGDISH KUMAR (American Institute of Physics, 1999)
To gain insight into the effects of the weakening of the electrostatic interactions on molecular dynamics when polar molecules are dissolved in a nonpolar solvent, the dielectric polarization and relaxation behaviors of iso-amylbromide and its 50 mol% solution in 2-methylpentane have been studied in detail over the frequency range, 1 mHz?1 MHz, and a temperature range approaching their liquid to glass transition. Features of the ~i! a-relaxation spectrum, ~ii! the Johari?Goldstein relaxation process in the liquid state at low temperatures, with an asymmetric spectral shape, and ~iii! the temperature dependence of the relaxation dynamics have been determined and the effects of weakening of the electrostatic interaction on these features examined. The high-frequency wing of the loss spectrum of the a-relaxation is proportional to v2b. The dynamics of its a-relaxation follows the Arrhenius equation initially at high temperatures and thereafter the Vogel?Fulcher? Tamman equation. Alternative equations for the change in the relaxation rate have been discussed. A decrease in the dipole?dipole interaction and reduction in the internal field in a solution with a nonpolar solvent leads to a remarkable change in the shape of the relaxation spectra at high frequencies such that the dielectric loss for the a-relaxation becomes proportional to v2ab, with a, b,1. The relaxation spectra of iso-amyl bromide dissolved in 2-methylpentane follows the H?N function and therefore behaves similar to a polymer, whereas for pure iso-amyl bromide follows the Davidson?Cole behavior.
PUBLISHED
Keywords: Condensed matter physics; dielectric relaxation